FPR2 Expression in Placental Extravillous Trophoblasts, and Its Relationship with Race, Delivery Mode, and Chorioamnionitis. (14th June 2022) - Sweeney, Sarah; VanOrmer, Matthew; Thompson, Maranda; Slotkowski, Rebecca; Freeman, Alyssa; Hergenrader, Alexandra; Paetz, Olivia; Wegner, Lauren; Ali, Khadijjta; Bender, Nicole; Chaudhary, Ridhi; Yuil-Valdes, Ana; et al.
Abstract: Objectives: Polyunsaturated fatty acids (PUFAs) are critical for appropriate development of the fetal brain and are known to reduce pregnancy complications like preeclampsia and preterm birth. Their benefits are thought to be mediated through bioactive metabolites; upon ingestion, PUFAs are converted to specialized pro-resolving mediators (SPMs). These SPMs resolve inflammatory processes by binding receptors, including the formyl-peptide receptor-2 (FPR2) in placental extra-villous trophoblasts tissue. The purpose of this study was to quantify FPR2 expression in placental tissue samples and correlate these levels with maternal-fetal outcomes and characteristics. Methods: Placental tissue samples were collected from postpartum mothers (n = 27) and stained for FPR2. QuPath was used to quantify FPR2 expression and determine the percentages of low, medium, and high expression in each sample. A Kruskal-Wallis test was performed to compare FPR2 expression across race. Mann-Whitney U-tests compared FPR2 expression from vaginal vs cesarean deliveries, and with vs without chorioamnionitis. A p-value < 0.05 was considered statistically significant. Results: There was a significant difference in distribution of % high FPR2 expression based on race and ethnicity. In post-hoc pairwise comparisons, Hispanic mothers had significantly higher % high FPR2 expression than White mothers (2.95%, 0.11%, p = 0.031) and African American mothers (2.95%, 0.10%, p = 0.049). Mothers who gave birth vaginally had a greater % high FPR2 expression, but this difference only approached significance (0.126%, 0.027%, p = 0.07). Mothers with chorioamnionitis also appeared to have a lower % medium FPR2 expression, but this difference did not reach statistical significance (7.16%, 13.62%, p = 0.076). Conclusions: This study demonstrates the potential role FPR2 plays in perinatal outcomes. Greater % high FPR2 expression in Hispanic mothers suggests a genetic upregulation of FPR2 expression. The data also suggests FPR2 expression may be related to clinical outcomes such as delivery mode and chorioamnionitis; however, further investigation with a higher sample size is warranted. Funding Sources: UNMC Pediatrics Department; Child Health Research Institute.